The Genus Pustulatirus Vermeij and Snyder, 2006 (Gastropoda: Fasciolariidae: Peristerniinae) in the Western Atlantic, with Descriptions of Three New Species - Lyons, William G.; Snyder, Martin Avery (Zootaxa, 2013)
Western Atlantic species of the New World genus Pustulatirus Vermeij and Snyder, 2006 are revised. Types of previously named taxa are figured. Species recognized as valid include P. attenuata (Reeve, 1847), range uncertain; P. eppi (Melvill, 1891), Curaçao; P. ogum (Petuch, 1979), northeastern Brazil; and P. virginensis (Abbott, 1958), Bahama Islands and east-ern Caribbean Sea to Aruba. Latirus karinae Nowell-Usticke, 1969 is confirmed as a junior subjective synonym of P. vir-ginensis. Syrinx annulata Röding, 1798, treated as a Caribbean Pustulatirus by Vermeij and Snyder (2006), and Latirus annulatus Melvill, 1891 are regarded as species inquirenda. Three new species are described: P. biocellatus, northeastern Brazil; P. utilaensis, Bay Islands, Honduras and northwestern Panamá; and P. watermanorum, Honduras continental shelf and offshore Colombian banks. Most western Atlantic Pustulatirus shells exhibit little intraspecific variability in morphol-ogy or color and occur within rather precise, well-defined ranges; an exception is P. virginensis, whose shells exhibit much variability in size, morphology and color.